2019
DOI: 10.1080/24750573.2019.1633007
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer, macular thickness and anterior segment measurements in attention deficit and hyperactivity disorder

Abstract: AIM: We aimed to explore whether there is difference in terms of Retinal Nerve Fiber Layer (RNFL) thickness, macula thickness and anterior segment structures of the eye between children and adolescents with ADHD and healthy controls. METHOD: Children and adolescents aged 8-16 years who were admitted to the Child Psychiatry outpatient clinic of Ahi Evran University Hospital diagnosed with ADHD constituted the study group. Exclusion criteria included patients who had any systemic/ocular or psychiatric disorder o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Eleven studies analyzing anatomic ocular measures in people with and without ADHD were included in the meta-analyses. Two for axial length [ 24 , 54 ], four for ganglion cell layer thickness [ 55 – 58 ], three for intraocular pressure [ 56 , 59 , 60 ], eight for macular thickness [ 30 , 54 , 56 59 , 61 , 62 ], two for macular volume [ 61 , 62 ] and eight for RNFL thickness [ 30 , 54 – 58 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies analyzing anatomic ocular measures in people with and without ADHD were included in the meta-analyses. Two for axial length [ 24 , 54 ], four for ganglion cell layer thickness [ 55 – 58 ], three for intraocular pressure [ 56 , 59 , 60 ], eight for macular thickness [ 30 , 54 , 56 59 , 61 , 62 ], two for macular volume [ 61 , 62 ] and eight for RNFL thickness [ 30 , 54 – 58 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bodur et al [ 55 ] reported significantly reduced optical nerve thickness in children with ADHD compared to those without. Ayyildiz et al [ 54 ] found increased corneal thickness and reduced corneal curvature radius in children with ADHD, but no significant differences in corneal diameter. Conversely, Ababneh et al [ 27 ] found no significant differences in corneal curvature power or maximum curvature power between children with and without ADHD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bodur et al (9) demonstrated that the GCL thickness of the ADHD group (mean age 111.62±27.05 months) was thinner than the control group. According to the study of Ayyildiz and Ayyildiz (10), corneal thickness was significantly higher in ADHD group (mean age 142.89±24.31 months) than in controls. Also, there was no discernible variation in RNFL thickness between groups.…”
Section: Introductionmentioning
confidence: 97%